Assessing zoonotic risk in a fenced natural park in northwestern Italy: integrating camera traps for a vector-host approach to investigate tick-borne pathogens - Vada, Rachele; Zanet, Stefania; Occhibove, Flavia; Trisciuoglio, Anna; Varzandi, Amir Reza; Ferroglio, Ezio (Frontiers in Veterinary Science, 2025)
Tick-borne diseases are among the major widespread emerging zoonotic diseases, and their circulation in the environment is influenced by a broad range of abiotic and biotic factors, including the abundance of vectors and vertebrate hosts. In this study, we estimated the prevalence of tick-borne pathogens and the impact of wildlife head count on their circulation in a lowland natural area in northwestern Italy. We collected ticks and camera trap pictures from 14 sampling points every 2 weeks for 1 year and identified pathogens through molecular analyses: Babesia capreoli, B. microti-like, Borrelia burgdorferi sensu lato (s.l.), Rickettsia of the spotted fever group (SFG), Theileria capreoli, and Anaplasma phagocytophilum. We modeled the presence of B. capreoli, B. microti-like, B. burgdorferi s.l., and SFG Rickettsia on head counts of wild ungulates and mesocarnivores. We tested a global model including all collected ticks, as well as a model focusing solely on Ixodes ricinus nymphs, the species, and the developmental stage most associated with zoonotic infection risk. The highest prevalence was obtained for B. microti-like (13%) and SFG Rickettsia (11%), and, for most pathogens, no differences were detected among tick species and their developmental stages. Mesocarnivores showed an additive effect on B. microti-like and B. burgdorferi s.l., while wild ungulates, non-competent for transmission of our target pathogens, showed a dilutive effect. These findings confirm the circulation of relevant tick-borne pathogens in the study area and show the use of camera trap data in predicting tick-borne pathogens’ risk by targeting host species which may have an indirect impact and are more easily addressed by monitoring and control strategies.